Roles of Ubiquitination and Deubiquitination in Regulating Dendritic Cell Maturation and Function - Zhu, Bo; Zhu, Lihua; Xia, Lin; Xiong, Yuyun; Yin, Qing; Rui, Ke (Frontiers in Immunology, 2020)
Dendritic cells (DCs) are specialized antigen-presenting cells that play a key role in immune homeostasis and the adaptive immune response. DC-induced immune tolerance or activation is strictly dependent on the distinct maturation stages and migration ability of DCs. Ubiquitination is a reversible protein post-translational modification process that has emerged as a crucial mechanism that regulates DC maturation and function. Recent studies have shown that ubiquitin enzymes, including E3 ubiquitin ligases and deubiquitinases (DUBs), are pivotal regulators of DC-mediated immune function and serve as potential targets for DC-based immunotherapy of immune-related disorders (e.g., autoimmune disease, infections, and tumors). In this review, we summarize the recent progress regarding the molecular mechanisms and function of ubiquitination in DC-mediated immune homeostasis and immune response.